Faktor yang mempengaruhi kebijakan dividen pada perusahaan manufaktur yang terdaftar di bei - Lidia, Agustine Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The objective of this research is to obtain empirical evidence on the influence of profitability, liquidity, leverage, firm growth, and firm size toward dividend policy. This study uses data from manufacturing companies listed on the Indonesia Stock Exchange during 2015-2017. The results of this study indicate that firm growth and firm size have a significant influence on dividend policy, while profitability, liquidity, and leverage have no significant influence on dividend policy. To further complement future research, make the sample count bigger, use companies that include not only manufacturing companies, and use variables that have not been used that may influence company’s dividend policy.